INTEGRATED APPROACH OF THE RISK AND ENVIRONMENTAL IMPACT. CASE STUDY – PREREQUISITES OF A NATECH EVENT AT A NATURAL GAS COMPRESSOR STATION - KOVACS, Alexandra; BICAN-BRIȘAN, Nicoleta; MALOS, Cristian; OZUNU, Alexandru (Studia Universitatis Babeș-Bolyai Ambientum, 2015)
The scope of the study which lies behind this paperwork is to emphasize the importance of integrated approach of risk and environmental impact, previous to and/or during the performance of an industrial activity. The case study analyzes gas compressor station located in an area that is subject to landslides. The geomorphologic risk analysis employed the methodology of the GT 019-98 standard. The outcome of such methodology has materialized in the elaboration of a risk map showing an average to high risk probability of landslide in the area where the compressor station is located. In order to assess the environmental impact an assessment matrix was applied, which shows that the activity at the location has significant impact on environment and on the people’s health and safety as well as on the land instability. Further to the integrated approach of the risk and environment impact an overall perception on the current environment issues from the location was outlined, and the importance of elaborating a NaTech type risk analysis for any industrial objective from the design phase was emphasized, providing the conditions for alignment to the sustainable development concept.